(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
The aim of this study is to attempt to define the content of the concept of food self-sufficiency as a determining factor in the modern concept of food security. The following methods were applied: functional analysis, comparative analysis, and communicative approach. For the first time, the essence and qualitative characteristics of the fundamental concept in food studies – food self-sufficiency – are defined. The essence and functions of food self-sufficiency are clarified. In contemporary conditions, food self-sufficiency appears to be a basic factor for the sustainable development of any society, state, and nation. Revealing its role and significance is a topical problem of scientific- theoretical research not only in the field of food studies but also in the social sciences.